Acid-Suppressive Drugs and Risk of Fracture in Children and Young Adults: A Meta-Analysis of Observational Studies - Li, Jiangbi; Xie, Xiaoping; Liu, Weibing; Gu, Feng; Zhang, Ke; Su, Zilong; Wen, Qiangqiang; Sui, Zhenjiang; Zhou, Pengcheng; Yu, Tiecheng (Frontiers in Pharmacology, 2021)
Background: Recent studies have suggested that proton pump inhibitors (PPIs) and histamine type 2 receptor antagonists (H2RAs) may increase the risk of fracture. We performed a meta-analysis to evaluate the risk of fracture with PPIs and H2RAs use in children and young adults. Methods: PubMed, EMBASE database, Cochrane Library, and Web of Science for relevant articles published before May 2021 were searched. We included all the observational studies reporting on the risk of fracture with acid-suppressive drug (PPIs and H2RAs) use in children and young adults. We calculated pooled risk ratios (RRs) for fracture using random-effects models and conducted subgroup analyses. Results: A total of six studies were included in our analysis. Pooled analysis of PPIs use showed significant risk for fracture (RR = 1.23; 95% CI, 1.12–1.34; I2 = 79.3), but not significant for PPIs combined with H2RAs use (RR = 1.22; 95% CI, 0.94–1.60; I2 = 44.0%), as well as for H2RAs use alone (RR = 1.08; 95% CI, 0.94-1.24; I2 = 84.1%). Grouping of studies by region showed a significantly increased fracture risk with PPIs use in North America (RR = 1.24; 95% CI, 1.16–1.32; I2 =0.0%) than in Europe (RR = 1.23; 95% CI, 1.00–1.52; I2 = 94.6%) and Asia (RR = 1.10; 95% CI, 0.96–1.25). However, there was no significant association between the H2RAs use and the fracture risk in North America (RR = 1.08; 95% CI, 1.00–1.09; I2 = 0.0%). Moreover, PPIs use showed an increased risk of fracture in women (RR = 1.13; 95% CI, 1.07–1.19; I2 = 0.0%), whereas there was no significant association between the PPIs use and the risk of fracture in men (RR = 0.93; 95% CI, 0.66–1.31; I2 = 0.0%). Conclusion: PPIs use alone could increase the risk of fracture in children and young adults, but not for PPIs combined with H2RAs use or H2RAs use alone. Clinicians should exercise caution when prescribing PPIs for patients.